Evaluation of fluid intake habit and fuid importance among middle age and elderly patients - Šilabritienė, Jolanta; Spirgienė, Lina (Slauga. Mokslas ir praktika, 2021)
The aim is to evaluate fluid intake and knowledge about fluid intake importance among middle age and elderly patients in emergency department.Methods. The study performed in emergency department. 110 patients participated in the study. Patients were divided in 2 groups according age group: 45–49 age (middle age) and ≥ 60 (elderlyAuthors according literature review made questionnaire). Bioethics persission was given by Lithuanian University of Health Sciences Bioethics center (No. BEC-SLF(N)-229).Results. Of all patients, 52.7 proc. were women and 47.3 proc. men. Water drink more women (82.8 proc.), patient with secondary education (84.0 proc) and living in countryside. Mineal water drink more men (36.5 proc.), patients with high education (38.2 proc.) and living in cities (39.1 proc.). During day 1.5–2 litres of fluid drink 28.2 proc. of patients (accordingly middle age 29.4 proc. and 27.1 proc. elderly). Only 1 litre of fluid drink more elderly patients than middle age (accordingly 32.2 proc. and 19.6 proc.). The most of patients (66.3 proc.) sometimes felt thirst during the day. Acoording the most (51.8 proc.) patients opinion (accordingly eldelry 57.6 proc. and middle age 45.1 proc.) people must intake 1.5–2 litred of fluid per day. The most (46.0 proc.) of middle age patients knew about fluid intake from Internet, the most of elderly (50,0 proc.) knew more from journals, magazines. Community nurses gave less information for middle age group and elderly patients (accordingly 6.3 proc. and 16.7 proc.).Conclusions. Patients of emergency department intake not enough fluid, even one third of elderly patients drink only less than 1 litre per day. The most popular fluid in both groups were water and tea. Patients the most information about fluid intake gave from Internet, publications, and least from community nurses.
Keywords: patients; fluid intake; knowledge